Molecular mechanisms regulating synaptic specificity and retinal circuit formation - Graham, Hannah K. (Wiley Interdiscip Rev Dev Biol, 2020)
The central nervous system (CNS) is composed of precisely assembled circuits which support a variety of physiological functions and behaviors. These circuits include multiple subtypes of neurons with unique morphologies, electrical properties, and molecular identities. How these component parts are precisely wired-up has been a topic of great interest to the field of developmental neurobiology and has implications for our understanding of the etiology of many neurological disorders and mental illnesses. To date, many molecules involved in synaptic choice and specificity have been identified, including members of several families of cell-adhesion molecules (CAMs), which are cell-surface molecules that mediate cell-cell contacts and subsequent intracellular signaling. One favored hypothesis is that unique expression patterns of CAMs define specific neuronal subtype populations and determine compatible pre- and postsynaptic neuronal partners based on the expression of these unique CAMs. The mouse retina has served as a beautiful model for investigations into mammalian CAM interactions due to its well-defined neuronal subtypes and distinct circuits. Moreover, the retina is readily amenable to visualization of circuit organization and electrophysiological measurement of circuit function. The advent of recent genetic, genomic, and imaging technologies has opened the field up to large-scale, unbiased approaches for identification of new molecular determinants of synaptic specificity. Thus, building on the foundation of work reviewed here, we can expect rapid expansion of the field, harnessing the mouse retina as a model to understand the molecular basis for synaptic specificity and functional circuit assembly. This article is categorized under: Nervous System Development > Vertebrates: General Principles Nervous System Development > Vertebrates: Regional Development